Essays on Common Institutional Ownership, Multiple Large Shareholders and Zero Leverage - REN, ZE (2024)
This thesis comprises a collection of three chapters that delve into significant aspects of corporate finance, exploring the impact of ownership structure, firms' financial decisions, and information asymmetry.